The Relationship between Parenting Style and Sexual Behavior before Marriage in Teenagers - Zubaidah Zubaidah; Insana Maria; Rusdiana Rusdiana (Universitas Airlangga, 2020)
Introduction: The purpose of this study was to learn about the relationship between parent style and sexual behavior before marriage among the teenagers in SMKN 3 Banjarbaru.Methods: The design of this study was analytical with a cross-sectional approach. The population consisted of 810 teen classes X, XI, XII with the sample totaling as many as 226 teen classes X and XII in SMKN 3 Banjarbaru. The sample was determined using a stratified random sampling technique. The independent variable was parenting style and the dependent variable was sexual behavior before marriage. The data was collected using a questionnaire. The analysis was done using Spearman Rho.Results: Sex before marriage is a bad behavior.Conclusion: There is a significant relationship between the parenting style used and sex before marriage in terms of the behavior of teenagers in SMKN 3 Banjarbaru